Pediatric HIV Infection Findings At The Time Of Diagnosis In A Tertiary Care Center In Turkey - Neslihan Mete Atasever; Elif Dede; Behiye Benaygül Kaçmaz; Ayper Somer; Selda Hançerli Törün (Journal of Global Antimicrobial Resistance)
AIM: The aim was to evaluate the clinical and laboratory data of pediatric patients with HIV infection at the time of diagnosis and to increase pediatric HIV awareness. BACKGROUND: HIV, one of the important public health problems seen all over the world, progresses more rapidly and mortality is higher in children. Higher viral loads are detected, more bacterial infections and opportunistic infections occur. Therefore, it is important to know the clinical findings well for early diagnosis. METHODS: The study included 73 children under the age of 18 who were followed up with the diagnosis of HIV infection at the Department of Pediatric Infection, Istanbul University, Istanbul Faculty of Medicine between 2000-2024. Age at diagnosis, immunological and clinical stages at diagnosis were retrospectively examined from patient files. Immunological and clinical staging of HIV was performed in accordance with the World Health Organization Classification. RESULTS: The mean age of 73 HIV-infected children at the time of diagnosis was 7.18±6.38 years (min:0 maks:17). Figure 1 shows the infection findings of the patients at the time of diagnosis; 18 were asymptomatic and had normal physical examinations. Clinical and immunological stages at the time of diagnosis are shown in Figure 2 and Figure 3, respectively. CONCLUSION: While the age of diagnosis was earlier in previous years due to mostly vertical transmission, the infection findings at the time of diagnosis and the clinical-immunological stages differ with the increasing positive adolescent population, therefore we think that our report is important for clinicians.